Tradisi Momulang dalam Perspektif Maqashid Syari’ah dan Prinsip Keadilan Hukum Nasional - Jihan Shafa Salsabila; Zeni Lutfiyah (Journal of Law, Society, and Islamic Civilization, 2025)
Marriage in Indonesia is influenced by the diverse cultures and customs of each region, one of which is the marriage tradition of the Sasak community in Lombok, known as the Momulang tradition. The Momulang tradition, also known as Merariq tradition, as a cultural identity of the Sasak community faces challenges regarding its compatibility with Islamic law and national law. This research aims to analyze the implementation of the Momulang tradition from the perspective of maqashid sharia and principles of justice in national law to ensure the preservation of the Momulang tradition in accordance with its surrounding legal framework. This study employs a socio-legal reserach with an interdisciplinary approach. Data collection techniques used in this legal writing include interviews, observations, and literature study. This research uses qualitative descriptive analysis techniques, describing the problems based on theory and findings in the field and explaining them through sentences against the data obtained. The results of this study indicate conflicts in the implementation of the Momulang tradition based on the five fundamental aspects of maqashid sharia, and its implementation needs to consider several aspects based on national legal justice principles, particularly the principle of equality.